Meeting climate-smart agriculture goals with agroforestry - World Agroforestry Centre (2019)
CSA programs aim to help smallholder farmers increase productivity while also building resilience and mitigating climate change. Agroforestry—the integration and use of trees in crop fields, farms and across agricultural landscapes—can support CSA in many ways, including: building resilience by buffering rising temperatures and conserving soil moisture; increasing soil carbon; improving soil health and fertility; providing fodder and shade for livestock; diversifying agricultural production and diets; and contributing to energy security and economic development. Agroforestry encompasses a diverse set of options tailored to local contexts. Options include a broad range of activities such as intensification of extensive parkland systems; multi-strata tree-cropping in coffee, cocoa and rubber plantations; and silvo-pastoral systems that integrate trees with livestock on rangelands. Successful implementation means finding the best practices to match the local environmental and social context. This brief offers an overview of the benefits of agroforestry to CSA.